2018
DOI: 10.1002/mrm.27188
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying myofiber integrity using diffusion MRI and random permeable barrier modeling in skeletal muscle growth and Duchenne muscular dystrophy model in mice

Abstract: The present study demonstrates that DTI at multiple diffusion times with the random permeable model analysis allows for noninvasively quantifying muscle fiber microstructural changes during both normal muscle growth and disease progression. Future studies can apply our technique to evaluate current and potential treatments to muscle myopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 79 publications
2
30
0
Order By: Relevance
“…The largest ADC differences were observed for diffusion times above 250 ms, which can only be achieved using stimulated echo‐based sequences . Such methods have been applied in ex‐vivo muscle studies,and more recently in animal and human muscle, but direct histological comparative data to support interpretation of diffusion imaging are sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest ADC differences were observed for diffusion times above 250 ms, which can only be achieved using stimulated echo‐based sequences . Such methods have been applied in ex‐vivo muscle studies,and more recently in animal and human muscle, but direct histological comparative data to support interpretation of diffusion imaging are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Early work applying diffusion measurements in skeletal muscle demonstrated that muscle fibres exhibit restricted diffusion behaviour . More recently, muscle structure and function have been increasingly investigated in both humans and animals using time dependence of diffusion parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A possible promising development could be using longer diffusion times with stimulated echo approaches because this allows modeling of membrane permeability and myofiber size, as recently shown in mouse models of DMD. 77,78 Current magnetic resonance perfusion MRI techniques allowing the noninvasive functional assessment of peripheral microvasculature in healthy and diseased individuals are blood oxygenation level-dependent (BOLD), arterial spin labeling (ASL), and dynamic contrast-enhanced (DCE) MRI. The functional imaging of skeletal muscle microvasculature helps in the understanding of muscular and vascular physiology and alterations of microcirculation under certain pathologic conditions such as peripheral arterial occlusive disease, diabetes mellitus, chronic compartment syndrome, and rheumatic disorders.…”
Section: P Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…32 This closely relates to permeability changes related to changes in muscle metabolism. 6 Additionally, damage found in dystrophin-deficient muscle 4,5 is thought to lead to mechanically-induced tears in the membrane, which can also be modeled as an increase in the average flux across the membrane. Bates et al 12 model permeability in this way as well, but they do not systematically examine its effect.…”
Section: Naughton and Georgiadismentioning
confidence: 99%
“…Excision and sectioning may also change the morphological features being examined. 6 Diffusion MRI (dMRI) is a promising noninvasive method that is sensitive to changes in the underlying microstructure. Much work has been done in brain matter to elucidate the relationship between the dMRI signal and the underlying microstructure.…”
mentioning
confidence: 99%